Waste Analysis in Warehouse Flow through the Lean Warehousing Approach: Analisis Pemborosan pada Aliran Pergudangan melalui Pedekatan Lean Warehousing - Annora Fitriasari; Dira Ernawati; Sinta Dewi (Academia Open, 2025)
General background: Efficient warehouse flow is essential for sustaining operational performance, yet many industrial warehouses still face substantial inefficiencies arising from non–value-added activities. Specific background: PT. XYZ’s raw material warehouse experiences systematic delays, administrative redundancies, and quality-control bottlenecks, reflected in high waiting time, frequent mismatches in material documentation, and 116 rejected materials in 2024. Knowledge gap: Despite the relevance of Lean Warehousing in reducing waste, limited studies examine its integrated application using VSM, PAM, VALSAT, and Fishbone analysis within cement-industry warehouses. Aims: This study aims to identify dominant sources of waste and develop targeted improvement strategies to streamline warehouse flow. Results: Current State Mapping revealed a total lead time of 422 minutes, with 79.4% of activities categorized as NVA and NNVA. The most critical wastes were waiting (18%), transportation (17%), and motion (16%). Implementing improvements—including digital verification, standardized routing, and process simplification—reduced lead time to 351 minutes, achieving a 16.8% efficiency gain. Novelty: This research integrates multi-tool Lean analysis to produce structured, evidence-based improvements tailored to raw-material warehouse operations. Implications: Findings demonstrate that Lean Warehousing substantially enhances warehouse reliability and can guide broader supply-chain optimization initiatives in similar manufacturing settings. Highlights: Identifies dominant wastes—waiting, transportation, and motion—as primary sources of inefficiency. Demonstrates that integrated Lean tools reduce lead time by 16.8%. Highlights the importance of digitalization to streamline warehouse processes. Keywords: Lean Warehousing, Waste Reduction, Value Stream Mapping, Process Activity Mapping, Warehouse Efficiency